Development of Model for Effective Waste Management on Community-Based Co-Production: A Case Study of Thailand - Amornsiriphong, Somsak; Chantrawarin, Yuthpong; Mulaphong, Dhanakorn; Poopan, Siwaporn; Koomklang, Jidapa; Ratanawijitrasin, Sauwakon; Rodsoodthi, Shannana; Petchtam, Khemtida (Journal of Ecohumanism, 2025)
This research critically examines the dynamics of community waste management, highlighting both the successes and persistent challenges in Tha Muang District, Kanchanaburi Province, Thailand. It aims to analyze the successes and challenges faced by local communities and administrative bodies in managing community waste, industrial waste, and infectious waste, as well as to develop a waste management model that increases community participation and co-production principles, with potential for adaptation in other areas facing similar contexts. Employing qualitative and area-based research methodologies, fieldwork was conducted from April 25 to October 30, 2022. The findings underscore critical waste management issues, such as budgetary shortfalls, inefficient processes, and a lack of adequate human resources. These challenges have undermined the community’s capacity to implement effective waste management solutions. In response, this research proposes a model grounded in the co-production framework, fostering a more symbiotic partnership between local communities and governmental authorities. The proposed model addresses structural deficiencies in budgeting, operational processes, and workforce management. Additionally, it advocates for a transformative approach that mitigates environmental impact and empowers communities to take a proactive role in sustainable waste management. By foregrounding these issues, the study highlights the urgent need for more integrative, community-driven solutions to enhance waste management systems in resource-limited settings.